2018
DOI: 10.1155/2018/4759232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Task Failure on Intermuscular Coherence Measures in Synergistic Muscles

Abstract: The term “task failure” describes the point when a person is not able to maintain the level of force required by a task. As task failure approaches, the corticospinal command to the muscles increases to maintain the required level of force in the face of a decreased mechanical efficacy. Nevertheless, most motor tasks require the synergistic recruitment of several muscles. How this recruitment is affected by approaching task failure is still not clear. The increase in the corticospinal drive could be due to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 65 publications
(83 reference statements)
3
6
0
Order By: Relevance
“…Here, most pronounced IMC was again evident in ES followed by TA, VM, and VL, as both ES and TA showed increases in IMC compared with VM and VL. Our findings add to previous evidence of beta IMC for ES ( Danna-Dos-Santos et al 2014 ), TA ( Boonstra et al 2008 , 2009 , 2015 ; Bravo-Esteban et al 2014 ), VM ( Boonstra et al 2008 ; von Tscharner et al 2018 ; Walker et al 2019 ), and VL ( von Tscharner et al 2018 ; Walker et al 2019 ), but were expected, as beta IMC has been commonly observed between synergistically activated muscles ( Boonstra 2013 ; Boonstra and Breakspear 2012 ; Castronovo et al 2018 ; Degani et al 2017 ; Kilner et al 1999 ). Beta IMC of the lower extremities has been described between homologous VM during bilateral leg extensions ( Boonstra et al 2008 ), as well as homologous VM and TA during standing ( Boonstra et al 2015 ), although not for homologous ES.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Here, most pronounced IMC was again evident in ES followed by TA, VM, and VL, as both ES and TA showed increases in IMC compared with VM and VL. Our findings add to previous evidence of beta IMC for ES ( Danna-Dos-Santos et al 2014 ), TA ( Boonstra et al 2008 , 2009 , 2015 ; Bravo-Esteban et al 2014 ), VM ( Boonstra et al 2008 ; von Tscharner et al 2018 ; Walker et al 2019 ), and VL ( von Tscharner et al 2018 ; Walker et al 2019 ), but were expected, as beta IMC has been commonly observed between synergistically activated muscles ( Boonstra 2013 ; Boonstra and Breakspear 2012 ; Castronovo et al 2018 ; Degani et al 2017 ; Kilner et al 1999 ). Beta IMC of the lower extremities has been described between homologous VM during bilateral leg extensions ( Boonstra et al 2008 ), as well as homologous VM and TA during standing ( Boonstra et al 2015 ), although not for homologous ES.…”
Section: Discussionsupporting
confidence: 88%
“…Apart from ES, gamma IMC has been observed in all other muscles recorded during this study, i.e., VM, VL ( Mohr et al 2015 , 2018 ; von Tscharner et al 2018 ), and TA ( Bravo-Esteban et al 2014 ; van Asseldonk et al 2014 ). Numerous studies have observed gamma IMC between muscle pairs of lower extremities ( Bravo-Esteban et al 2014 ; Castronovo et al 2018 ; De Marchis et al 2015 ; Mohr et al 2015 , 2018 ; van Asseldonk et al 2014 ; Walker et al 2019 ), although, to the best of our knowledge, this is the first study to demonstrate gamma IMC between homologous muscles of lower extremities. With these results, we extend findings by Mohr and colleagues ( Mohr et al 2015 , 2018 ), who originally observed gamma IMC between VM and VL during isometric as well as dynamic BpS.…”
Section: Discussionmentioning
confidence: 68%
“…The studies propose that the degree of correlation that is recorded between the different muscle activities can advertise the co-activation of functional, and it may be extended to functionally similar and anatomically close muscles (13,36) or functionally different and anatomically distant (37). The pair-wise coherence can also be modeled as two terms summation: The one just related to the muscles pair considered (residual) with excluding the third one effects and the one relative to the whole synergy (pair-wise) but with elements synchronized to the third muscle involved activity (31). According to this claim, the pair-wise coherence decline could be explained either by the contribution of coherence decreasing relative to the drive of synergistic (all three muscles common command) or by volley desynchronization that is solely common to the two muscles (31).…”
Section: Discussionmentioning
confidence: 99%
“…The pair-wise coherence can also be modeled as two terms summation: The one just related to the muscles pair considered (residual) with excluding the third one effects and the one relative to the whole synergy (pair-wise) but with elements synchronized to the third muscle involved activity (31). According to this claim, the pair-wise coherence decline could be explained either by the contribution of coherence decreasing relative to the drive of synergistic (all three muscles common command) or by volley desynchronization that is solely common to the two muscles (31).…”
Section: Discussionmentioning
confidence: 99%
“…Three muscles were estimated using the pool coherence function to find out the common neural coupling between each of two muscle groups (i.e., group A and group B) (35), which is defined as:…”
Section: Beta-band Intermuscular Coherence Analysismentioning
confidence: 99%